2020
DOI: 10.1080/21663831.2020.1778111
|View full text |Cite
|
Sign up to set email alerts
|

Direct conversion of Teflon into nanodiamond films

Abstract: We report a novel nonequilibrium approach for direct laser writing diamond by melting amorphous polytetrafluoroethylene (PTFE:(C 2 F 4) n) in ambient conditions. The nanosecond laser pulses disintegrate PTFE, forming the undercooled molten carbon. This undercooled molten carbon regrows into diamond during the ultrafast melt quenching process, which lasts for ∼ 100 ns. HRTEM imaging, SAED, Raman, and EEL spectroscopy investigations confirm the first-order phase transformation of PTFE into single-crystalline < 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 32 publications
2
12
0
Order By: Relevance
“…Our study involves regrowth of the undercooled BN melt (193 nm laser source) and ref involves localized laser heating (532 nm laser source) of the pre-existing c-BN nanoparticles. From our previous experiments and simulations on the C system, ,, we found that undercooling packs up the molten carbon making the simulation results obtained under HPHT conditions match with the results of the undercooled liquid-quenching experiments. Hence, the motivation toward employing the ExTEP pseudopotential, which works better under HPHT conditions and is reliable to simulate melting characteristics of c-BN and h-BN.…”
Section: Resultssupporting
confidence: 69%
“…Our study involves regrowth of the undercooled BN melt (193 nm laser source) and ref involves localized laser heating (532 nm laser source) of the pre-existing c-BN nanoparticles. From our previous experiments and simulations on the C system, ,, we found that undercooling packs up the molten carbon making the simulation results obtained under HPHT conditions match with the results of the undercooled liquid-quenching experiments. Hence, the motivation toward employing the ExTEP pseudopotential, which works better under HPHT conditions and is reliable to simulate melting characteristics of c-BN and h-BN.…”
Section: Resultssupporting
confidence: 69%
“…[ 160 ] The phase transition of carbon through radical or transient intermediates also has been shown to have profound impacts on the final allotrope of the carbon product, [ 161 ] and further work has shown that fluorination of the substrate can result in increases in radical stability during phase transformations. [ 162,163 ] Thus, FJH of fluorinated organic carbon precursors was probed and resulted in controllable phase evolution. Fluorinated substrates included the use of Teflon and other perfluoroalkyl species.…”
Section: Extensions and Outlook Of Flash Joule Heatingmentioning
confidence: 99%
“…Laser irradiation is a novel method for synthesizing ND film with non-high temperature and non-high pressure. To date, many materials including graphite carbon, polytetrafluoroethylene (PTFE) was conducted to synthesize the ND films through the excimer pulsed laser annealing technology [ 27 , 28 , 81 , 82 ]. In 2014, Nian Q. et al explored a confined pulsed laser deposition (CPLD) technique with the order of nanosecond to produce the patterned ND films from a layer of graphite topped with a glass cover sheet at room temperature and normal pressure [ 27 ].…”
Section: Fabrication Methods and Nucleation Process Of Nanodiamond Filmmentioning
confidence: 99%
“…Despite of the graphite carbon, PTFE, commercially known as the Teflon, are used as the carbon source in the formation of ND films [ 28 , 81 ]. Gupta S. et al reported a direct argon fluoride excimer pulsed laser annealing (PLA) writing method for ND film with shorter duration (~100 ns) via melting PTFE in ambient condition in 2020, where the laser energy density is maintained at 1 J/cm 2 .…”
Section: Fabrication Methods and Nucleation Process Of Nanodiamond Filmmentioning
confidence: 99%